2019
DOI: 10.1101/19006833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reproductive Factors and Risk of Breast Cancer by Tumor Subtypes among Ghanaian Women: A Population-based Case-control Study

Abstract: Background Higher proportions of early onset and estrogen receptor (ER) negative cancers are observed in women of African ancestry than in women of European ancestry. Differences in risk factor distributions and associations by age at diagnosis and ER status may explain this disparity. Methods We analyzed data from 1,126 women (aged 18 to 74 years) with invasive breast cancer and 2,106 population controls recruited from three hospitals in Ghana from 2013 to 2015. Odds ratios (OR) and 95% confidence intervals … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…Despite heterogeneity in parity-related exposures, the differential effect of parity by ER has been consistently reported across different populations ( 26), ( 22), ( 20), (27). Although we were not able to compare relative risks associated with parity in different molecular subtypes due to the case-only design, our results of higher parity in ER negative than in ER positive patients is consistent with results from previous case-control studies (20), (27).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Despite heterogeneity in parity-related exposures, the differential effect of parity by ER has been consistently reported across different populations ( 26), ( 22), ( 20), (27). Although we were not able to compare relative risks associated with parity in different molecular subtypes due to the case-only design, our results of higher parity in ER negative than in ER positive patients is consistent with results from previous case-control studies (20), (27).…”
Section: Discussionsupporting
confidence: 88%
“…Investigations of associations between breastfeeding and breast cancer risk by receptor status have resulted in inconsistent ndings, with some showing similar protective effect for all subtypes (30), and others showing a stronger protection against ER negative especially TNBC (31). In the Ghana study in which the frequency of ER negative breast cancer especially TNBC was higher (28% vs 18% of tumors) than in the Kenya study, the increased risk of parity was offset by more extended breastfeeding, which was only seen among patients < 50 years of age in ER negative but not in ER positive patients; while in older women, extended breastfeeding showed an inverse association regardless of ER status yet a stronger association for ER positive patients (20). We did not observe signi cant differences of breastfeeding by ER or by intrinsic subtype, either in all women or by age.…”
Section: Discussionmentioning
confidence: 92%
“…We used multivariable polytomous logistic regression to estimate associations of the microbiota parameters (alpha diversity, beta diversity, and taxa relative abundance or presence/absence) with breast cancer and nonmalignant breast disease. We also estimated associations of alpha and beta diversity with breast cancer grade (grade 1 and 2 or grade 3) and subtype, focusing our analyses on the most common subtypes (estrogen receptor [ER] −/+, triple‐negative (ER−, PR−, and HER2−), and luminal‐like A (ER+ or PR+ and HER2−) 4 ) and tested for heterogeneity by grade/subtype using a case‐only multivariable logistic regression analysis with grade/subtype as the dependent variable. For all alpha diversity analyses, we categorized participants into tertiles of the alpha diversity metrics based on the distribution among the controls.…”
Section: Methodsmentioning
confidence: 99%
“…Women of African ancestry tend to be diagnosed with breast cancer at younger ages, at a later stage, and with more aggressive subtypes than women of non‐African ancestry 1,2 . Increasing breast cancer incidence in sub‐Saharan Africa is likely due to the adoption of Westernized lifestyles, changes in reproductive factors and population aging (due to increased life expectancy) 2‐4 . However, breast cancer risk factors remain understudied among African populations.…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, Figueroa et al showed that increased parity (≥3 births) was associated with a reduced risk of both ER+ and ER− breast cancer among women aged 50+ but was associated with an increased risk of early onset ER− tumours. Extended breastfeeding was also associated with a protective effect for both ER+ and ER‐ breast cancer, although the protective effect was stronger for ER+ tumours 34 . In a small Ugandan hospital‐based study, no differences in distribution of reproductive risk factors by ER status were found among breast cancer cases 35 …”
Section: Discussionmentioning
confidence: 95%